Extending Long‐Term Avian Studies Alters Temporal and Climate‐Driven Trend Conclusions - Irene Zanandrea; Juan Moreno; Alejandro Cantarero (Ecology and Evolution)
ABSTRACT Long‐term population studies are crucial for understanding the impacts of climate change on biodiversity; however, predictions based on short‐term data may be unreliable. Here, we analyse yearly averages of reproductive parameters (laying date, nestling condition, and female condition) of a Pied Flycatcher (Ficedula hypoleuca) population in central Spain across one, two, and three decades of study to evaluate how study duration affects conclusions about population trends. Our findings reveal that initial trends deduced from studies of shorter duration often weaken, invert, or disappear when extended durations are included. For example, advancements in laying dates only become apparent after more than two decades, while trends in nestling and female condition vanish over time. Additionally, we observed unexpected responses, such as delays in laying during exceptionally hot prelaying periods. These results emphasize the necessity of long‐term studies spanning multiple generations to accurately assess the impacts of climate change and inform effective conservation strategies. Our work underscores the risks of relying on short‐term data to predict long‐term ecological trends.